Environment and landscape management during the Middle Neolithic in Southern France: Evidence for agro-sylvo-pastoral systems in the Middle Rhone Valley - Delhon, Claire; Thiébault, Stéphanie; Berger, Jean-François (Quaternary International, 2009)
Rescue excavations in the Middle Rhone Valley have provided opportunities to develop innovative strategies for the study of palaeoenvironments. These strategies involve sampling and analysis of botanical remains, recovered not only from archaeological sites but also in ‘‘off-site’’ pedosedimentary sequences thought to be poor in botanical remains. Thus, these remains (phytoliths, pedocharcoal) give access to unexplored depositional contexts, such as alluvial plains. Moreover, off-site data are useful because they minimise the hazard of cultural bias (e.g., selection of species during wood gathering). Comparison of data collected in the alluvial plain with data obtained via anthracological analyses of karstic caves and rock-shelters in the hinterland suggests a complex agro-sylvopastoral management of the landscape during the Middle Neolithic. We propose a pattern that supposes considerable specialization in use of plains vs. slopes in the landscape, and a strong and continuous human pressure on the vegetation and soils between 4500 and 3500 cal BC. Nevertheless, these constraints are not sufﬁcient to explain the persistence of such a system for more than a millennium. Favourable climatic conditions are thought to have been a determining factor in the persistence of an ecologically meta-stable relationship between human societies and their natural environment.
Keywords: CHARCOAL ANALYSIS; Middle Neolithic; Middle Rhone; oak; vegetation dynamics (citation)

Environment and landscape management during the Middle Neolithic in Southern France: Evidence for agro-sylvo-pastoral systems in the Middle Rhone Valley - Delhon, Claire; Thiébault, Stéphanie; Berger, Jean-François (Quaternary International, 2009)
Rescue excavations in the Middle Rhone Valley have provided opportunities to develop innovative strategies for the study of palaeoenvironments. These strategies involve sampling and analysis of botanical remains, recovered not only from archaeological sites but also in ‘‘off-site’’ pedosedimentary sequences thought to be poor in botanical remains. Thus, these remains (phytoliths, pedocharcoal) give access to unexplored depositional contexts, such as alluvial plains. Moreover, off-site data are useful because they minimise the hazard of cultural bias (e.g., selection of species during wood gathering). Comparison of data collected in the alluvial plain with data obtained via anthracological analyses of karstic caves and rock-shelters in the hinterland suggests a complex agro-sylvopastoral management of the landscape during the Middle Neolithic. We propose a pattern that supposes considerable specialization in use of plains vs. slopes in the landscape, and a strong and continuous human pressure on the vegetation and soils between 4500 and 3500 cal BC. Nevertheless, these constraints are not sufﬁcient to explain the persistence of such a system for more than a millennium. Favourable climatic conditions are thought to have been a determining factor in the persistence of an ecologically meta-stable relationship between human societies and their natural environment.
Keywords: CHARCOAL ANALYSIS; Middle Neolithic; Middle Rhone; oak; vegetation dynamics (citation)

Long-Term Observation of Mediterranean Ecosystems with Satellite Remote Sensing - Hill, Joachim; Hostert, Patrick; Röder, Achim (Recent Dynamics of the Mediterranean Vegetation and Landscape, 2005)
This chapter contains sections titled: * Introduction * Remote Sensing Concepts * The Analysis of Environmental Change with Landsat Satellites * Discussion * Acknowledgements
Keywords: earth observation satellites; Landsat data; Linear Spectral Mixture Analysis; Mediterranean ecosystems; NOAA-AVHRR1 satellite system; satellite remote sensing; semi-natural ecosystems; SPOT-satellite; vegetation dynamics (citation)

Long-Term Observation of Mediterranean Ecosystems with Satellite Remote Sensing - Hill, Joachim; Hostert, Patrick; Röder, Achim (Recent Dynamics of the Mediterranean Vegetation and Landscape, 2005)
This chapter contains sections titled: * Introduction * Remote Sensing Concepts * The Analysis of Environmental Change with Landsat Satellites * Discussion * Acknowledgements
The following values have no corresponding Zotero field: periodical: Recent Dynamics of the Mediterranean Vegetation and Landscape electronic-resource-num: 10.1002/0470093714.ch4
Keywords: earth observation satellites; Landsat data; Linear Spectral Mixture Analysis; Mediterranean ecosystems; NOAA-AVHRR1 satellite system; satellite remote sensing; semi-natural ecosystems; SPOT-satellite; vegetation dynamics (citation)